Olivia-- and the missing toy - Falconer, Ian, 1959- (New York : Atheneum Books for Young Readers, 2003)
When her best toy mysteriously disappears, Olivia the feisty pig is determined to find out who is responsible.
"An Anne Schwartz book."
AD 210
Adult 210
Accelerated Reader AR
Keywords: Lost articles -- Juvenile fiction; Toys -- Juvenile fiction; Swine -- Juvenile fiction